Efficacy of Pelvic Repositioning Exercises on Pain, Hip and Shoulder Range of Motion and Disability of the Patients with Chronic Nonspecific Low Back Pain: A Single Blinded Randomized Controlled Trial - Noureddin Karimi; Mehran Fathizadeh; Mohammad Reza Nourbakhsh; Akbar Biglarian (Shiraz University of Medical Sciences, 2021)
Background: Chronic non-specific low back pain (LBP) is one of the mostcontroversial issues of experts. Positive Ober`s test was considered a contributingfactor to LBP. Common intervention to address such problems was surgery oriliotibial band stretching. Recently, it was suggested that pelvic malalignmentis the contributing factor to Positive Ober`s test. Pelvic repositioning exerciseswas argued as a solution for the treatment of chronic LBP followed by pelvicmalalignment.Methods: In this single-blinded randomized controlled trial, 18 patientsparticipated and were assigned into the control and treatment groups using theblock randomization method. One side Positive Ober`s test as an indicator ofpelvic malalignment was used as an inclusion criterion to employ the patientswho have pelvic malalignment and asymmetry. Patients were asked to completethe Oswestry disability questionnaire to assess their disability. Hip internal andexternal rotation and shoulder internal and external rotation ROM measured bya standard goniometer. An inclinometer measures hip adduction and abductionROM. Outcome measures were reassessed after 12 days. Data were analyzedusing the ANCOVA test to compare among groups.Results: Patients in treatment group showed significant improvement of pain(P=0.01), ipsilateral hip adduction (P=0.00) and internal rotation (P=0.02)ROM and contralateral hip abduction (P=0.00) and shoulder internal rotation(P=0.00) ROM and Glenohumeral internal rotation deficit (GIRD) (P=0.001)compared with control group. There was no difference among groups fordisability (P=0.34) and contralateral hip external rotation (P=0.06) and alsothere was no difference for contralateral shoulder external rotation (P=0.85) andipsilateral shoulder internal (P=0.13) and external rotation (P=0.58).Conclusion: Pelvic repositioning exercises are an effective treatment to reducechronic LBP via improving pelvic alignment. These exercises improve GIRD andincrease shoulder internal rotation ROM, contralateral to positive Ober`s test.2021© The Authors. Published by JRSR. All rights reserved.